Política de formação continuada : um estudo da escola de agentes leigos de Vacaria/RS (1986-1995) - Rossi, Cláudia Adriana Zamboni (2013)
The rescue of Theology Of Liberation in which its methodological processes prioritizes a new way of being church, presents the experience of non-formal education as an alternative in order to develop proposals for Continuing Education, where the protagonists are individuals involved in the educational process. One of these spaces were constituted by schools of training lays between the years 1970 and 1980 in several Brazilian dioceses. This research is focused in the Diocese of Vacaria, Rio Grande do Sul state, where in 1988 began an experience of popular education with the creation of a School of Pastoral Agents (EAP) for Catholic layman. In this sense, theoretical support was sought in popular education, that would allow the awareness of individuals about their reality and their practices. The focus on the research consists of investigating the development of the School layman of Pastoral agents, from the Diocese of Vacaria: the topics worked, the methodology used, the impact of training the staff that took part . In the reconstruction and understanding of this experience of popular education, it has been used a dialectic approach, in which the analysis of the experience was proceeded as a whole, its advances, conflicts and contradictions. Different sources were analyzed, including documents from the records of the Diocese N.Sra Oliveira; interviews with the coordinators of the school, written records resulting from systematization performed in different stages of the course. Thus, this paper shows how the continued training of the layman Pastoral Agents influenced the everyday actions of the individuals participating in the local community